Direct oral anticoagulants versus warfarin for venous thromboembolism prophylaxis in nephrotic syndrome patients: a retrospective study - Ahmed El-Bardissy; Mohamed Nabil Elshafei; Hebatullah Abdelgawad; Rana Mekkawi; Asma Eltahir; AbdulMoqeeth Mohammed; Ashour AM; Hazem Elewa (Thrombosis Journal)
Abstract Background Nephrotic syndrome (NS) is associated with an increased risk of venous thromboembolism (VTE). Anticoagulants are widely used in the prevention of VTE in NS patients. The use of direct oral anticoagulants (DOACs) has not been studied intensively in NS patients. The aim of this study is to determine the efficacy and safety of DOACs compared to warfarin for prophylactic anticoagulation in patients with nephrotic syndrome. Methods Retrospective analysis conducted in a tertiary hospital-based ambulatory anticoagulation clinic between 01/07/2016 and 29/11/2021. We aimed to evaluate the incidence of VTE, major bleeding, and non-major bleeding in both the DOACs and warfarin groups. Results Fifty-seven patients were recruited, 31 patients were prescribed warfarin (54.4%), and 26 were on DOAC (45.6%). Two patients in the DOAC group developed VTE, while no subjects in the warfarin group developed VTE, however, the difference was not statistically significance (p = 0.2). Nine out of 31 patients in the warfarin group developed non-major bleeding compared to three patients in the DOAC group (p = 0.02). One patient developed major bleeding in each group DOAC group 1 (15.4%), warfarin 1 (12.9%) (p = 1.00). There was no statistically significant difference in major bleeding between DOAC and warfarin groups (p = 1.00). Conclusion In patients with NS, preliminary evidence suggests that DOACs have comparable efficacy as compared to warfarin when used as prophylaxis. Additionally, DOACs result in lower incidences of non-major bleeding. However, further studies are indicated to confirm the superiority of DOACs over warfarin.